What are the Effects of Outsourcing Primary care? Evidence from Healthcare Center Procurements - Herzig, Mikko (My University, 2023)
Multiple municipalities in Finland have chosen to outsource their healthcare centers to private entities with increasing outsourcings in scale and size. However, little is known about the causal effects of these outsourcings on costs and quality of healthcare. This thesis investigated these effects by utilizing quasi-experimental methods in a staggered setting with similar data and time frame as previous studies. The results indicate: 1) Outsourcings might result in short-time savings driven mostly by the healthcare savings, while the longer-term effects and origins of these savings remain more unclear. However, as not all of the results were statistically significant, a null effect cannot be ruled out. 2) The results were mostly robust to wide variety of robustness checks and alternative samples. 3) No change in quality was observed, but these findings were limited by the data.
Keywords: public economics, outsourcing, public procurement, health economics